Ecological stoichiometric characteristics of three dominant fish species from the Beibu Gulf: inter- and intraspecific variations - Wang, Caiguang; Zhu, Liang; Huang, Liangliang; Xu, Hao; Xu, Peng; He, Xiongbo; Yan, Yunrong; Yang, Xi; Shahab, Asfandyar; Kang, Bin (Frontiers in Ecology and Evolution, 2023)
In this study we explore the inter- and intraspecific variations in the ecological stoichiometry of three dominant fish species (Saurida tumbil (n = 33), Pennahia macrocephalus (n = 34), and Upeneus sulphureus (n = 32)) from the Beibu Gulf, the contents of carbon (C), nitrogen (N), phosphorus (P), calcium (Ca), δ13C, and δ15N in fishes were analyzed. Results illustrated that the ranges of elemental variations (C, N, P, and Ca) in the three fishes were 36.73%~49.24%, 8.79%~13.99%, 1.11%~2.78%, and 1.16%~4.58%, respectively while P content varied the most, resulting in variations in C:P and N:P in fishes. Correlation analysis determined the association among various parameters and illustrated that Ca content was significantly positively correlated with P content, which indicated that P content variation was attributed to the formation of fish bones and scales. The C, N, and P contents and their ratios were significantly correlated with body length and δ13C in the three fishes, indicating that the changes in C:N:P concentrations are due to individual development and food sources. Significant inter- and intraspecific differences in the body stoichiometry of the three fishes were found in this study, mainly due to differences in body size and diet. The aquatic organisms underwent individual development fluctuations in morphology and diet, which consequently altered their stoichiometric features.